2022
DOI: 10.1002/clc.23799
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 in the prediction of heart failure and death in patients with atrial fibrillation

Abstract: Background: Biomarkers may be a useful marker for predicting heart failure (HF) or death in patients with atrial fibrillation (AF).Hypothesis: Soluble ST2 (sST2) may be a good biomarker for the prediction of HF or death in patients with AF.Methods: This is a prospective study of patients with nonvalvular AF. Clinical outcomes were HF or death. Clinical and laboratory data were compared between those with and without clinical outcomes. Univariate and multivariate analysis was performed to determine whether sST2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The included studies used various sources of sST2 reagents and adopted diverse detection strategies (e.g., 15 studies used ELISA to detect sST2, 2 used aspect plus assay, 1 used plasma samples assay, and 1 used duoset immunoassay assay). Concerning the purpose of these studies, 12 studies ( 12 , 13 , 21 , 24 , 25 , 27 , 28 , 32 , 34 37 ) evaluated the predictive value of sST2 in occurrence of AF, while 8 studies ( 14 , 19 , 20 , 22 , 26 , 29 , 31 , 33 ) evaluated AF recurrence, 5 studies ( 17 , 18 , 23 , 30 , 37 ) evaluated MACEs following AF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies used various sources of sST2 reagents and adopted diverse detection strategies (e.g., 15 studies used ELISA to detect sST2, 2 used aspect plus assay, 1 used plasma samples assay, and 1 used duoset immunoassay assay). Concerning the purpose of these studies, 12 studies ( 12 , 13 , 21 , 24 , 25 , 27 , 28 , 32 , 34 37 ) evaluated the predictive value of sST2 in occurrence of AF, while 8 studies ( 14 , 19 , 20 , 22 , 26 , 29 , 31 , 33 ) evaluated AF recurrence, 5 studies ( 17 , 18 , 23 , 30 , 37 ) evaluated MACEs following AF.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 diaplayed the characteristics of the included studies for predictive value of sST2 in MACEs following AF. Five studies ( 17 , 18 , 23 , 30 , 37 ) with 1,614 AF patients examined the relationship between sST2 and the risk of MACEs following AF. The pooled analysis of the estimates as a continuous variable indicated that sST2 was significantly associated with the risk of MACEs (HR:1.60, 95% CI: 1.13–2.27, P < 0.01; I 2 = 82.0% Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…39 Levels of ST2 are known to increase significantly in both heart failure and AF. 40,41 Here, marked enlargement of the atria of rabbits in the RAP group was seen on echocardiography, a clear indication of structural remodeling, and the LVEF was also reduced, although it did not reach the degree of HFrEF and worsening of HF. CVF levels also increased significantly in the RAP group, shown by, and western blotting and biochemical assays demonstrated raised levels of collagens I and III and ST2 in the RAP group, an indication that atrial fibrosis was a consequence of rapid pacing.…”
Section: Discussionmentioning
confidence: 92%
“…Based on the characteristics of sST2, sST2 is considered an important prognostic indicator for patients with heart failure, and sST2 is also considered an important marker for monitoring the treatment of patients with HF, especially the risk of patients with chronic heart failure combined with end-stage renal failure receiving hemodialysis or AHF combined with renal insufficiency 14,15 . In patients with atrial fibrillation, diagnosis can be more accurately determined from sST2 levels alone than with NT-ProBNP by itself or with the two readings in combination 16 . Although there were many studies on the effect of ST2 as a biomarker, researchers have not yet reached a consensus on the specific mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In patients with atrial fibrillation, diagnosis can be more accurately determined from sST2 levels alone than with NT-ProBNP by itself or with the two readings in combination. 16 Although there were many studies on the effect of ST2 as a biomarker, researchers have not yet reached a consensus on the specific mechanism of action. In view of several recent studies, the role of ST2 may be related to inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%